Picture This... Developing Standards for Electronic Images at the National Library of Medicine - Masys, Daniel R. (1990)
New computer technologies have made it feasible to represent, store, and communicate high resolution biomedical images via electronic means. Traditional two dimensional medical images such as those on printed pages have been supplemented by three dimensional images which can be rendered, rotated, and “dissected” from any point of view. The library of the future will provide electronic access not only to words and numbers, but to pictures, sounds, and other nontextual information. There currently exist few widely-accepted standards for the representation and communication of complex images, yet such standards will be critical to the feasibility and usefulness of digital image collections in the life sciences. The National Library of Medicine is embarked on a project to develop a complete digital volumetric representation of an adult human male and female. This “Visible Human Project” will address the issue of standards for computer representation of biological structure.